Analisis kemampuan Komunikasi Matematis Pada Materi Bilangan Berpangkat Dan Bentuk Akar Di Kelas IX SMP Negeri 10 Padang - Yulla Tifa; Zulfitri Aima; Alfi Yunita (Horizon, 2022)
This research is motivated by the low mathematical communication skills of students in solving problems of mathematical communication skills, especially in learning mathematics. This study aims to determine how students' mathematical communication skills on the matter of numbers with powers and forms of roots. This type of research is descriptive quantitative research. The subjects of this research were eighth grade students of SMP Negeri 10 Padang. Subjects were taken with 20 students by giving a test of mathematical communication skills, then from these results 3 research subjects were selected based on the categories of low, medium, and high abilities. The results of this study showed that the achievement of the indicators of students' mathematical communication skills. In the indicator of connecting real objects, images or equations into mathematical form are in the high category with a percentage of 78%, explaining mathematical situations and relations orally or in writing using algebraic forms, pictures, or equations are in the medium category with a percentage of 47%, and changing real events into mathematical language and symbols are in the medium category with a percentage of 65%. Keywords: Mathematical Communication, Powers and Roots